Geometric Features of the Pial Arteriolar Networks in Spontaneous Hypertensive Rats: A Crucial Aspect Underlying the Blood Flow Regulation - Lapi, Dominga; Di Maro, Martina; Serao, Nicola; Chiurazzi, Martina; Varanini, Maurizio; Sabatino, Lina; Scuri, Rossana; Colantuoni, Antonio; Guida, Bruna (Frontiers in Physiology, 2021)
Several studies indicate that hypertension causes major changes in the structure of the vessel wall by affecting the regulation of blood supply to the tissues. Recently, it has been observed that the capillary blood flow is also considerably influenced by the structural arrangement of the microvascular networks which undergo rarefaction (reduction of the perfused vessel number). Therefore, this study was aimed to assess the geometric arrangements of the pial arteriolar networks and the arteriolar rhythmic diameter changes in spontaneously hypertensive rats (SHR). Method: Fluorescence microscopy was utilized to in vivo observe the pial microcirculation through a closed cranial window. Pial arterioles were classified according to Strahler’s method. The arteriolar rhythmic diameter changes were evaluated by a generalization short time Fourier transform. Young SHRs showed four orders of vessels while the adult ones only three orders. The diameter, length and branching number obeyed Horton's law; therefore, the vessels were distributed in a fractal manner. Larger arterioles showed more asymmetrical branches than the smaller ones in young SHRs while in adult SHRs the smaller vessels presented asymmetrical branchings. In adult SHRs there was a significant reduction in cross-sectional area compared with young SHR: this implies an increase in peripheral resistance. Young and adult age-matched normotensive rats did not show significant alterations in the geometric arteriolar arrangement with advancing age, both had 4 orders of arteriolar vessels and the peripheral resistance did not change significantly. Conversely, the frequency components evaluated in arteriolar rhythmic diameter changes of young and adult SHRs showed significant differences, because of a reduction in the frequency components related to endothelial activity detected in adult SHRs. In conclusion, hypertension progressively causes changes in microarchitecture of the arteriolar networks with a smaller number of vessels and consequent reduced conductivity, characteristic of rarefaction. This was accompanied by the reduction in the formation and release of independent- and dependent-endothelial nitric oxide components regulating arterial vasomotion.